Photoactivated disinfection procedure for denture stomatitis in diabetic rats - Zhang, Xiao; Zhao, Zirui; Zhang, Ruiqi; Liu, Juan; Guo, Zhijiao; Hu, Qiaoyu; Liu, Na; Liu, Qing (PeerJ, 2024)
Objective To study the efficacy of PADTM Plus-based photoactivated disinfection (PAD) for treating denture stomatitis (DS) in diabetic rats by establishing a diabetic rat DS model. Methods The diabetic rat DS model was developed by randomly selecting 2-month-old male Sprague-Dawley rats and dividing them into four groups. The palate and denture surfaces of rats in the PAD groups were incubated with 1 mg/mL toluidine blue O for 1 min each, followed by a 1-min exposure to 750-mW light-emitting diode light. The PAD-1 group received one radiation treatment, and the PAD-2 group received three radiation treatments over 5 days with a 1-day interval. The nystatin (NYS) group received treatment for 5 days with a suspension of NYS of 100,000 IU. The infection group did not receive any treatment. In each group, assessments included an inflammation score of the palate, tests for fungal load, histological evaluation, and immunohistochemical detection of interleukin-17 (IL-17) and tumor necrosis factor (TNF-α) conducted 1 and 7 days following the conclusion of treatment. Results One day after treatment, the fungal load on the palate and dentures, as well as the mean optical density values of IL-17 and TNF-α, were found to be greater in the infection group than in the other three treatment groups (P < 0.05). On the 7th day after treatment, these values were significantly higher in the infection group than in the PAD-2 and NYS groups (P < 0.05). Importantly, there were no differences between the infection and PAD-1 groups nor between the PAD-2 and NYS groups (P > 0.05). Conclusions PAD effectively reduced the fungal load and the expressions of IL-17 and TNF-α in the palate and denture of diabetic DS rats. The efficacy of multiple-light treatments was superior to that of single-light treatments and similar to that of NYS.
Keywords: Candida albicans; Photoactivated disinfection; Diabetes mellitus; Denture stomatitis; IL-17; TNF-α